Three approaches to radiocarbon calibration of amino acid racemization in Mulinia lateralis from the Holocene of the Chesapeake Bay, USA - Simonson, Amy E.; Lockwood, Rowan; Wehmiller, John F. (Amino Acid Racemization, 2013)
A radiocarbon-calibrated aminochronology, based on the bivalve Mulinia lateralis, is presented for Chesapeake Bay core MD03-2661, a 25 m piston core drilled near Kent Island (38°53.21′N; 76°23.89′W) during the 2003 USGS Marion-Dufresne cruise. Three separate approaches were used to calibrate amino acid racemization (AAR) data for aspartic acid with radiocarbon data. For the first approach, a direct or paired analysis calibration incorporated eight articulated specimens, thereby allowing for the application of AAR and radiocarbon analysis of the same specimen and effectively eliminating both intrashell variability and time averaging as factors in the calibration. A second direct approach relied on valves that were bilaterally split to facilitate both AAR and radiocarbon dating, thus effectively eliminating time averaging effects from this calibration. For the third indirect approach, nine independent radiocarbon dates were combined with 129 Asx D/L ratios from the same core depths to produce an indirect calibration model, from which intershell variability and time averaging could be estimated. Variability in AAR ratios was recognized from a myriad of sources, including analytical error, intrashell variability, inherent variability, time averaging, and contamination. The majority of this variability was controlled for through experimental design or by the application of these three independent calibration approaches. The direct calibration of articulated shells and the indirect calibration yielded virtually identical age models, well within their respective 95% confidence intervals. This study establishes an aminostratigraphic reference section for the Holocene record of the Chesapeake Bay and demonstrates the usefulness of multiple calibration approaches and the potential utility of AAR for future studies of sedimentary processes and chronologies in the bay.
id: 2292

Central Arctic paleoceanography for the last 50 kyr based on ostracode faunal assemblages - Poirier, Robert K.; Cronin, Thomas M.; Briggs Jr, William M.; Lockwood, Rowan (Marine Micropaleontology, 2012)
The paleoceanography of the central Arctic Ocean was reconstructed for the last 50 kyr (Marine Isotope Stages (MIS) 1–3) based on ostracode assemblages from 21 14C-dated sediment cores from the Mendeleev, Lomonosov, and Gakkel Ridges. Arctic sediments deposited during the Holocene interglacial period (MIS 1), the Bølling–Allerød, and larger interstadial Dansgaard–Oeschger (DO) events (3–4, 8, and 12) contain abundant Cytheropteron spp., Henryhowella asperrima, and Krithe spp. at intermediate/deep-depths (~ 1000 to 3000 m). These assemblages suggest a ventilated deep, Arctic Ocean water mass similar to the modern Arctic Ocean Deep Water (AODW) during these time periods. In contrast, sediment deposited during stadial events corresponding to Heinrich events 1, 2, 3, and 4, (also possibly the Younger Dryas; YD), contain abundant Polycope spp. (60–80%) suggesting a greater influence of the Atlantic Layer (AL) on the Arctic Intermediate Water (AIW) and AODW. Reduced sea-ice during the early Holocene, the last deglacial, and MIS 3 interstadials is indicated by the reoccurrence of Acetabulastoma arcticum, an epipelagic species that is parasitic on sea-ice dwelling amphipods. One hypothesis to explain these oceanographic changes during longer stadial events, particularly within the last glacial period (MIS 2), involves sluggish ocean circulation, thicker sea-ice cover, and a deeper halocline with ocean exchange between Greenland Sea and Arctic Ocean deep-water through the Fram Strait.
id: 2283